Effusion cytology : a practical guide to cancer diagnosis - Ganjei-Azar, Parvin (Demos Medical, 2011)
Today, cytology of body cavity fluids is an integral part of cancer staging. A positive diagnosis indicates a high-stage (III or IV) cancer in a majority of instances. General pathologists and cytotechnologists rely on routine cytomorphologic criteria to help oncologists in their staging of cancer patients. The diagnostic clarity, however, is challenged by many false negatives and occasional false positive results. The former is usually followed by an unnecessary surgical procedure in the case of an under-staged cancer and the latter may prevent treatment of a potentially curable disease due.